Types and abundance of periphyton attached to the bamboo substrates in Lake Bakuok Aur Sati Village, Tambang District, Kampar Regency, Riau Province - Sihombing, Djob Fernadi; Simarmata, Asmika Harnalin; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPeriphyton is a microorganism that attached to a submerged substrate. This research  aims to determine the trophic state of the inundated area in Bakuok Lake, Aur Sati Village on periphyton abundance. This research has been conducted in June-July 2019. There were 3 stations, namely S1 (settlements area and closed to palm plantation area), S2 (restaurant and settlements area), S3 (around the floating net cages area). In each station there were two sampling points, namely in the surface (15 cm depth) and 2 Secchi depths (174 cm depth). The substrate used is a bamboo substrate (10x11 cm2). Substrate placement done 1 week before sampling. Sampling were conducted 3 time, once/week. The periphyton samples were obtained by spraying the bamboo surface with aquadest using a plastic sprayer. The periphyton were preserved with lugol 1% was then identified and the abundance of periphyton (APHA, 2012) was calculated. Water quality parameters measured were temperature, transparency, depth, pH, dissolved oxygen, free carbondioxide, nitrate and phosphate. Results shown that there were 25 types of periphyton, belongs to 5 classes, namely Bacillariophyceae (16 types), Chlorophyceae (4 types), Cyanophyceae (2 types), Zygnematophyceae (2 types), and Eugelenophyceae (1 type). Periphyton abundance found during the study ranged from 1,928-8,558 cells/cm2. The most common periphyton type was Melosira granulata. Based on the type of periphyton, it was concluded that the area in Bakuok Lake, Aur Sati Village can be catagorized as eutrophic.  Keywords: Types, abundance, Melosira granulata, eutrophic